Peran Faktor Persalinan terhadap Stunting pada Balita: Studi di Desa Tasikmadu, Indonesia : The Role of Delivery Factors on Stunting in Toddlers: A Village Study Tasikmadu Village, Indonesia - Della Kurnia Fauziah; Nurul Pujiastuti; Fitriana Kurniasari Solikhah; Tri Nataliswati (Fakultas Keperawatan Universitas Andalas, 2023)
Stunting remains a persistent nutritional challenge in Indonesia, posing a substantial threat to child growth and survival, typically manifesting in the second year of life. Its primary antecedent is inadequate prenatal protein intake, resulting in shortened birth length and increased susceptibility to stunting. This study aimed to elucidate the relationship between birth length and stunting among toddlers within Tasikmadu Village, employing a retrospective cohort design with a total sample size of 128 individuals selected through Total Sampling. The analysis of the collected data yielded a noteworthy result, with a calculated p-value exceeding 0.570. This outcome signifies the absence of a statistically significant correlation between birth length and the incidence of stunting among the study participants in Tasikmadu Village. Instead, the investigation highlights the prominence of postnatal factors as significant determinants of stunting prevalence. These factors include the untimely introduction of complementary foods alongside breastfeeding (MP-ASI), irregular MP-ASI feeding schedules, a predominantly carbohydrate-based MP-ASI menu, erratic breastfeeding timings, and premature discontinuation of exclusive breastfeeding. In summary, this study discerns a conspicuous dissociation between birth length and stunting occurrence in Tasikmadu Village. The implication is that the roots of stunting lie predominantly in postnatal practices, emphasizing the critical role of addressing issues such as inappropriate MP-ASI practices and breastfeeding patterns to effectively combat the prevalence of stunting among toddlers. These findings contribute to a more nuanced understanding of the multifaceted nature of stunting in this context, guiding future interventions and public health initiatives aimed at its mitigation.